Social Ethos in the Cross-History of Islam: An Analysis of the Medina Charter: Etos Sosial Dalam Lintas Sejarah Islam Studi Analisis Piagam Madinah - Edwin Jeri; Sartika Fortuna Ihsan; Faisal Efendi; Anton Akbar; Ikhwanuddin Abdul Majid; Nurlaila Nurlaila (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
This study aims to explore the contribution of the Medina Charter in shaping the social ethos of society at that time and its relevance in the context of modern society. It connects the spiritual and social dimensions of the Medina Charter with contemporary social challenges, as well as how these values can be adapted to strengthen solidarity and tolerance in today's society. This study provides new insights into the application of Islamic social ethos in creating a more just and prosperous social life. Using a library research approach, this study analyzes the Medina Charter as a document that contains important social values such as solidarity, cooperation, justice, and respect for differences. The Medina Charter, compiled by the Prophet Muhammad SAW, not only serves as a legal foundation but also as a source of inspiration in creating a more harmonious and inclusive social life, despite religious and ethnic diversity. Social ethos values in the Medina Charter that support the creation of a balance between rights and obligations, as well as how these principles are relevant to the formation of social ethics in modern societies that are increasingly fragmented and tense.